Culture Acculturation in Architecture of Masjid Kasimuddin at Bulungan, North Borneo - Afifah Nurul Jihad; Agus Dody Purnomo (Jurnal PATRA, 2022)
Acculturation is the process of mixing or merging two different cultures into one new culture. One example of cultural acculturation is found in the architecture of Kasimuddin mosque located in Tanjung Palas, Bulungan Regency, North Kalimantan has a unique architectural form. This mosque is often known as the sultan's mosque because this mosque was built during the Bulungan Sultanate. The existence of this mosque is included in the Bulungan government's cultural tourism project plan. In addition to having a local cultural character, the architecture of this mosque is also influenced by other cultures. This research aims to examine cultural acculturation in the architecture of Kasimuddin Mosque. In addition, it is expected that this writing can be one of the references for the implementation of the next mosque restoration. The research method used is qualitative method. With the form of data collection through field surveys, interviews, and some references from journals. This research was conducted on the Kasimuddin Mosque building. This mosque became one of the artifacts of the Bulungan sultanate and currently still serves as a place of worship as well as a cultural object. Various cultures influence the architecture of the mosque, including Javanese, Sumatran, Betawi, Malay, and European cultures. The occurrence of cultural acculturation because it is located in a coastal area where the area becomes a meeting place between nations. So it is not surprising that in the Bulungan area there is acculturation of different cultures. Kasimuddin Mosque is one example of the result of cultural acculturation. As a cultural heritage building is expected to always be maintained, and considered both by the local government and the local community.